Adsorption Isotherm for Copper-Benzotriazole System in HCl - Singh, A.K.; Singh, B.K. (Asian Journal of Chemistry, 2010)
The adsorption for copper benzotriazole system is presented. Upon analysis it shows that the adsorption is due to Frumkin. During the analysis relative size has been taken into account.